2016
DOI: 10.1590/2359-3997000000192
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hypothyroidism with levothyroxine plus liothyronine: a randomized, double-blind, crossover study

Abstract: Objective: To compare the effects of a unique fixed combination levothyroxine/liothyronine (LT4/LT3) therapy in patients with primary hypothyroidism. Subjects and methods: This is a randomized, double-blind, crossover study. Adults with primary hypothyroidism (n = 32, age 42.6 ± 13.3, 30 females) on stable doses of LT4 for ≥ 6 months (125 or 150 μg/day) were randomized to continue LT4 treatment (G1) or to start LT4/LT3 therapy (75/15 μg/day; G2). After 8 weeks, participants switched treatments for 8 more weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 46 publications
0
36
0
Order By: Relevance
“…Bunevicius et al described an increase in well-being, mood and psychometric functionality in patients treated with LT4/LT3 treatment (66), and two other studies also showed similar beneficial effect (67,68). Those findings could not be further replicated by other studies (69,70,71,72,73). The study with the largest sample size, 697 patients, and longest follow-up was conducted by Saravanan and coworkers.…”
Section: Combination Treatment With Lt4 and Lt3mentioning
confidence: 98%
“…Bunevicius et al described an increase in well-being, mood and psychometric functionality in patients treated with LT4/LT3 treatment (66), and two other studies also showed similar beneficial effect (67,68). Those findings could not be further replicated by other studies (69,70,71,72,73). The study with the largest sample size, 697 patients, and longest follow-up was conducted by Saravanan and coworkers.…”
Section: Combination Treatment With Lt4 and Lt3mentioning
confidence: 98%
“…Studies comparing QoL, mood and cognitive outcomes and patients' preference for treatment with LT4/LT3 combination therapy versus LT4 monotherapy are described in Table 1. 22,31,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] Among these 17 studies, 1 older study using very high LT4 and LT4/LT3 doses found that LT4 monotherapy had a more favourable adverse event profile and was preferred by patients versus LT4/LT3 combination therapy. 54 This study should likely be viewed from a historical perspective only because the conditions of treatment are dissimilar to the more modern studies listed below.…”
Section: Individual Studiesmentioning
confidence: 99%
“…22,42 The results of 10 studies, however, were neutral, finding no consistent advantage for monotherapy or combination treatment. 31,[46][47][48][49][51][52][53]56,57 Thus, the comparisons of LT4/LT3 combination therapy versus LT4 monotherapy produced mixed and equivocal results. It should be noted that there were large placebo effects in two of these studies: one that found an advantage with LT4/LT3 combination treatment and one in which results did not favour either treatment.…”
Section: Individual Studiesmentioning
confidence: 99%
See 2 more Smart Citations